TINJAUAN FILOSOFIS PROBLEMA PENGELOLAAN SAMPAH - Muthmainnah, Lailiy (Jurnal Filsafat "WISDOM", 2008)
AbstractModernisation as a term refers to the development processwhich has a lot of limitation, and one of this problem is aboutgarbage. Commonly, there are two big sources of garbage,industrializations and high mass consumtions. In fact, both of them are consequence of logical modernity. There are two reasons why garbage becomes a great problem in recent years. First, the quantity of garbage is overload, and second, its quality: most of the garbage is not bio-degradable. This problem will be more complicated because people usually use logic ânot in my back yardâ with their garbage. To respond this problem, modernity tries to transform in a new kind of development, that is usually called sustainable development. Although there are several different interpretations of sustainable development but it refers to The Brundtland Commission which defines sustainable development as a process of change in which the exploitation of resources, direction of investments, orientation of technological development, and institutional change are made consistent with future as well as present needs. For instance emphasize constancy of natural capital stock as a necessary condition for sustainability. Growth or wealth must be created without resources depletion. Exactly how this is to be achieved remains a mystery, but majority of sustainable development literature said that this condition will be achieved with using model ecological modernisation. Thus, the challenge is to find new technologies and to expand the role of the market in allocatingenvironment resources with the assumption that putting a price on the natural environment is only the way to protect it. In fact, this ways are used to solve the problem of garbage in recent years.Keywords: sustainability, ecology, garbage.